Successful Treatment of Myocardial Bridge with Alcohol Septal Ablation in Hypertrophic Obstructive Cardiomyopathy - Sunbul, Murat; Kepez, Alper; Tigen, Kursat; Erdogan, Okan; Mutlu, Bulent (International Journal of Angiology, 2014)
Hypertrophic obstructive cardiomyopathy (HOCM) is characterized by left ventricular hypertrophy of various morphologies, with variety of clinical manifestations and hemodynamic dysfunctions. Myocardial bridge (MB) is frequently seen in HOCM patients and the decrease of flow in the coronary artery segment going intramurally through the myocardium beneath a muscle bridge is also associated with angina, myocardial ischemia, arrhythmia, and sudden death in these patients. We present here a rare case of successful treatment of MB with alcohol septal ablation in hypertrophic cardiomyopathy which has not been reported previously.
Keywords: hypertrophic cardiomyopathy; alcohol septal ablation; myocardial bridge